2019
DOI: 10.1016/j.matdes.2019.107968
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Work of Fracture parameters for 3D printed polymer sheets

Abstract: Additive manufacturing is becoming increasingly popular in academia and industry.Accordingly, there has been a growing interest in characterizing 3D printed samples to determine their structural integrity behaviour. We employ the Essential Work of Fracture (EWF) to investigate the mechanical response of polymer sheets obtained through additive manufacturing. Our goal is twofold; first, we aim at gaining insight into the role of fibre reinforcement on the fracture resistance of additively manufactured polymer s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…PLA has a low glass transition temperature (60°C–70°C typically) and the MPDSM structure could weaken as the temperature rises, causing creep (in the best case) or disintegration (in the worst case). This is the reason that the raster-45° configuration is commonly used for PLA; it is generally considered to be the most stable configuration (Patterson et al , 2019; Ahmed and Susmel, 2017; Song et al , 2017; Cuesta et al , 2019; Papon and Haque, 2019).…”
Section: Design Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…PLA has a low glass transition temperature (60°C–70°C typically) and the MPDSM structure could weaken as the temperature rises, causing creep (in the best case) or disintegration (in the worst case). This is the reason that the raster-45° configuration is commonly used for PLA; it is generally considered to be the most stable configuration (Patterson et al , 2019; Ahmed and Susmel, 2017; Song et al , 2017; Cuesta et al , 2019; Papon and Haque, 2019).…”
Section: Design Studiesmentioning
confidence: 99%
“…However, there are the following three major issues with this approach for the problem at hand: First, the having all of the fibers facing in the same direction of the load may decrease the stiffness of the clip significantly due to fiber relaxation and pullout. Next, every layer in the structure would be a series of concentric rings, so any small manufacturing defects or fiber relaxation could case it to collapse. PLA has a low glass transition temperature (60°C–70°C typically) and the MPDSM structure could weaken as the temperature rises, causing creep (in the best case) or disintegration (in the worst case). This is the reason that the raster-45° configuration is commonly used for PLA; it is generally considered to be the most stable configuration (Patterson et al , 2019; Ahmed and Susmel, 2017; Song et al , 2017; Cuesta et al , 2019; Papon and Haque, 2019). …”
Section: Design Studiesmentioning
confidence: 99%
“…Nevertheless, it can sometimes be adopted in other geometries. For example, EWF methodology can be used in deeply double-edge notched small punch (DDEN-SP) test [ 14 ] and single-edge notched bending (SENB) as well [ 15 ]. EWF can be a simple alternative method for the J-integral under plane strain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease of 11% was observed in fracture toughness for printing orientation of 0/90°compared to + 45/− 45°. Recently, Cuesta et al [44] used the essential work of fracture (EWF) approach to examine the mechanical behaviour and fracture properties of 3D-printed polymeric materials, including fibre-reinforced plastics, and proposed a new miniature test specimen for measuring the fracture properties of polymers processed via AM. Moreover, Lorenzo-Bañuelos et al [45] examined the effect of raster orientation on the fracture properties of thin polypropylene (PP) components processed via material extrusion AM, and found that the printing orientation can have a significant effect on the essential work of fracture of the 3D-printed PP.…”
Section: Introductionmentioning
confidence: 99%